Epigenetic mechanisms underlying age-associated loss of human oocyte quality - Jorge, Inês Tavares de Sá (2022)
It is known that the ovarian aging displays a much faster rate of aging than any other body tissue, which leads to a reproductive outcome that is negatively correlated with age. Since women nowadays tend to postpone motherhood, it became crucial to understand the mechanisms underlying the decreasing oocyte quality. From the age of 30 onwards there are signs that precede the decline in fertility and the decrease in oocyte quality, but the mechanisms underlying this decay aren’t yet fully understood. Both methylation and demethylation of DNA, acetylation and deacetylation of histones are examples of epigenetic mechanisms that were described as being associated with the aging of the oocytes. The main objective of this study was to unravel possible epigenetic alterations in the ovarian human tissue and its contribution for the age-associated loss of human oocyte quality. In this study, a total of 30 samples were collected and three groups, taking into account female ages, were established. The gene expression analysis of the genes involved in methylation and hydroxymethylation and genes involved in histone deacetylation and histone acetylation was performed. Both DNMTs and TETs revealed a tendency to be altered between the 3 different groups of age ranges. DNMTs revealed a tendency to be more expressed in the younger group and, in fact, proper methylation establishment in the oocyte stages is crucial for a normal oogenesis. Regarding TET1 and TET2, it was observed a tendency to a decreased expression of group 2 when compared to group 1. On the other hand, TET3 showed a propensity to decrease its expression from group 1 to group 3. TETs family appears to play a crucial role in meiotic progression and in the oocyte quality, accelerating ageassociated infertility. Amongst HATs family, HAT1 showed a tendency to increase its level of expression from group 1 to 3 and, on the contrary, KAT6B and KAT8 showed a predisposition to decrease the expression level from group 1 to group 2. In fact, growing oocytes are in a transcriptionally active state and might need the enzymes responsible for chromatin remodeling. In an opposite way, HDACs, SIRT1 and SIRT2 revealed to have a proclivity to decrease the expression from group 1 to group 2, followed by a slight increase in the expression level of both genes in group 3. These genes are associated with the reduction of ovarian reserve and has also been shown to regulate proliferation and apoptosis in granulosa cells, or promote luteinisation. In conclusion, the absence of a significant association between gene expression levels and the three groups can be justified by the reduced number of samples or by the action of another epigenetic mechanism. It is essential to carry out more epigenetic studies and invest in statistical significance in human oocyte samples. This way, the understanding of these epigenetic mechanisms could enable a support to assisted reproductive technologies.